Molecular identification of Echinococcus granulosus isolates from ruminants in Greece - Roinioti, Erifylli; Papathanassopoulou, Aegli; Theodoropoulou, Ioanna; Simsek, Sami; Theodoropoulos, Georgios (Elsevier, 2016)
Cystic echinococcosis is a parasitic disease caused by Echinococcus granulosus, a cestode with worldwide distribution. Data on the circulating Echinococcus granulosus genotypes in Greek livestock is scant. The aim of the present study was to conduct a genetic analysis of 82 Echinococcus granulosus isolates from ruminants in Greece, including areas which until today have not been the subject of studies. The analysis relied on a PCR assay targeting cytochrome c oxidase, subunit 1 gene (CO1), followed by bidirectional sequence analysis of the amplification product. Eighty (n = 80) of the 82 (97.6%) isolates were allocated to Echinococcus granulosus sensu stricto (G1-G3) and were classified in 13 distinct haplotypes (9 common and 4 novel) with 12 polymorphic sites. The presence of the dominant haplotype EG1 as was documented in the European populations, was indicated in the country. Almost all regions shared the same common haplotype. In comparison to this predominant haplotype, the number of the nucleotide changes in all the other haplotypes ranged from 1 to 5. All nucleotide changes proved to be transitions (A <-> G or C <-> T). Two fertile hydatid cysts of sheep origin in different areas (Arkadia, Ilia) of the Peloponnese were identified as Echinococcus canadensis (G7 genotype). (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Echinococcus granulosus; Genotype; Haplotype; Ruminants; Greece